Response of Four O’clock Flowers (Mirabilis jalapa L.) to the Short Length of Illumination (Photoperiodism) - Hanik, Nur Rokhimah; Armania, Vallery; Hidayad, Muhammad Nur; Saputra, Dian Andhi; Mardyah, Muthia (Jurnal Biologi Tropis, 2024)
Long photoperiods can delay flower initiation and slow down the formation of flower primordia, so they can delay flowering. This study aims todetermine the photoperiodism response of four o'clock flowers (Mirabilis jalapa L.) to the short length of irradiation. The research was carried out for 3months (April-June 2024) and specifically data collection was carried out on 8 June 2024 in Bulurejo village, RT.03 RW. 04, Karangmojo, Weru District,Sukoharjo Regency, Central Java. From 05.53 WIB to 17.30 WIB. Samples of 15 plants growing in Bulurejo village, observed when the flowers bloom. Datawere analysed descriptively qualitative and combined with literature studies. The results of research on 15 plants of four o'clock flower (Mirabilis jalapa L.),the same species and location of four o'clock flower blooming turned out to be different times even though the difference was only slight. The average time ittakes to bloom is 10 hours 42 minutes. Further research needs to be done with a variety of different flowers, not only red flowers, but plus white, red andmixed colours with varied village locations, especially at differentaltitudes.Four o'clock flower (Mirabilis jalapa L) is a member of the family Nyctaginaceae, order Centrospermae, and is easy to grow in the yard withoutmuch care.